1998
DOI: 10.1086/517074
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Vancomycin‐Resistant Enterococcus faecium Isolated in Argentina

Abstract: as vanC1 and vanC2 probes [8, 9]. DNA from the clinical faecium Isolated in Argentina isolate hybridized to the vanA probe but not to vanB, vanC1, or vanC2 intragenic probes. Vancomycin-resistant enterococci (VRE) have been re-The patient was treated with piperacillin/tazobactam, ciported increasingly since 1988 [1]. Most of the early isolates profloxacin, chloramphenicol, and gentamicin. He underwent of VRE were from Europe, but the prevalence of VRE associbrain surgery, and two of the three abscesses were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
0
13
0
3
Order By: Relevance
“…In South America (Brazil and Argentina), vancomycin-resistant (VR) enterococcal infections have been described since 1998 (9,20). In a prospective multicenter surveillance study conducted in 2003, the prevalence of VR among enterococci in Colombia was found to be lower (9.7%) than that in the United States (1), and the isolation of similar percentages of VR enterococci has been described more recently (21).…”
mentioning
confidence: 99%
“…In South America (Brazil and Argentina), vancomycin-resistant (VR) enterococcal infections have been described since 1998 (9,20). In a prospective multicenter surveillance study conducted in 2003, the prevalence of VR among enterococci in Colombia was found to be lower (9.7%) than that in the United States (1), and the isolation of similar percentages of VR enterococci has been described more recently (21).…”
mentioning
confidence: 99%
“…faecium 10/96A was isolated in August 1996 from the blood of a 9-year-old girl with aplastic anemia (6). It was the first glycopeptide-resistant enterococcus isolated in Brazil and probably the first isolated in South America, predating by 1 month a VanA strain reported from Argentina (10). Susceptibility to glycopeptides was determined with E-tests (Cambridge Diagnostics Ltd., Cambridge, United Kingdom) on Diagnostic Sensitivity Test agar (Oxoid, Basingstoke, United Kingdom) containing 5% lysed horse blood.…”
mentioning
confidence: 99%
“…The prevalence of vancomycin-resistant enterococci (VRE) associated with nosocomial infections in the United States increased from 0.3% in 1989 to 7.9% in 1993. J In Argentina, the first infection produced by vancomycinresistant Enterococcus faecium was documented by Marin et al in 1996, 2 and even though other strains of VRE continue to be isolated, they have not been reported in the literature (MEDLINE, 1996(MEDLINE, -2000. The real prevalence of the intestinal carriage of VRE in Argentina is still unknown.…”
Section: E T T E R S T O T H E E D I T O R Detection Of Carriage Ofmentioning
confidence: 99%
“…1 The expanded regimen of three antiretroviral medications, including a protease inhibitor, is indicated after a high-risk exposure. 1,2 Because of good oral absorption and low reported side effects, nelfinavir is one of the recommended protease inhibitors. Commonly reported side effects involve mild abdominal cramps and diarrhea, which usually can be relieved by over-the-counter remedies.…”
Section: E T T E R S T O T H E E D I T O R Detection Of Carriage Ofmentioning
confidence: 99%